DASAR HUKUM PENGORBANAN BINATANG SAPI PADA UPACARA MUNGKAH WALI DI DESA TAMBAKAN DALAM TEKS-TEKS AGAMA HINDU - I Ketut Wardana Yasa (VYAVAHARA DUTA, 2024)
Cow sacrifices in religious ceremonies still occur in Tambakan Village, Kubutumbahan subdistrict, Buleleng Regency at the Bhuta Yajña ceremony called Masegeh which is a series of the Mungkah Wali Ceremony. Cows in Hindu scripture sources explain that both male and female cattle are highly respected and exalted. The majority of the people of Tambakan Village still support and believe in the implementation of this ritual, however written literary sources have not been found regarding the use of cows in the Masegeh ceremony at Prajapati Temple in Tambakan Village. Hindus in Tambakan village believe this only based on gugon tuwon and traditions passed down from generation to generation which they are still afraid of breaking. Beliefs that are not based on correct understanding and sources will lead to gaps in religious implementation or practice. For this reason, there is a need for a more in-depth study of the use of cows based on sacred scriptural sources, both Sruti and Smṛti, so that Hindus, especially in Tambakan Village, gain a more precise understanding regarding the use of cows in the Mungkah Wali ceremony. The aim of this research is to find out and analyze the legal basis from the Śruti books on the use of cows in the Mungkah Wali ceremony as well as the legal basis from the Smṛti book on the use of cows in the Mungkah Wali ceremony. This research is qualitative research with a religious phenomenology approach. The results of this research show that there are two main bases for cow sacrifice in the Hindu scripture texts, namely the Sruti texts and the Smerti texts. Basically, from these two texts it is found that female cows are highly venerated like mothers because they produce milk and male cows can be sacrificed if based on the correct methods and goals of sacrifice. The sacrifice of bulls at the Mungkah Wali Ceremony in the Tambakan traditional village from the results of observations and interviews and study of religious literary sources can be concluded that the sacrifice followed the correct sacrificial procedures according to Hindu religious literature. Keywords: Legal Basis, Sacrifice, Cow and Mungkah Wali